Sharp injuries during clinical training among medical students in the University of Peradeniya, Sri Lanka - Dalugama, Chamara; Gamage, Kavishka (International Journal of Occupational Safety and Health, 2023)
Introduction: Medical students are exposed to blood and body fluids during their clinical training which increased the risk of transmission of blood-borne infections. The objective of the study is to assess the prevalence, knowledge, attitudes and practices regarding sharp injuries among final medical students of the University of Peradeniya, Sri Lanka Methods: A survey was done among 210 final-year medical students of the University of Peradeniya with a self-administered online questionnaire including demographic information, experience, knowledge and reporting behavior following sharp injuries. Results: Response rate was 80% (n=168). Sharp injuries were experienced by 22.6%. Most of the sharp injuries were sustained during venepuncture (39.5%). The majority (58.9%) did not adhere to universal precautions as they did not anticipate the event. One-third of the students (31.6%) did not know about universal precautions. Most of the students (68.4%) who had a sharp injury did not seek post-exposure assistance or prophylaxis. The majority of this group thought there is no risk (64%). Twenty-five students have not completed the full course of the hepatitis B vaccine. More than half (51.8%) of the fully vaccinated group were unaware of their immune status. The majority (67.3%) believed that their knowledge is not adequate regarding the prevention and management of needle stick injuries. The majority (97%) believed more emphasis should be given to knowledge and practice regarding sharp injuries. Conclusion: The knowledge, attitudes and practices of medical students regarding the prevention and management of sharp injuries were unsatisfactory. Poor awareness was observed regarding immune status following hepatitis B vaccination among medical students.